Cyber Attack on Saudi Aramco - Alshathry, Sahar (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2017)
Saudi Aramco is the largest oil production company in the entire world. It supplies almost almost 1/10th of the oil in the world. The economy of Saudi Arabia is highly dependent on the production of oil. Aramco got attacked by a virus named Shamoon on 15th August 2012. It was one of the most disrupting cyber-attack that was carried out against the business. Shamoon had spread from the network of the company and it wiped out the hard drives of the computers. The virus infected almost thirty thousand of workstations during the mid of August . The paper will discus the impact of the cyber attack on the oil production on Saudi Aramco. In addition, the analysis and the mechanisms that the attackers used to launch the virus. This research explains how Saudi Aramco recovered form the cyber attack.